Immune alterations in recurrent implantation failure. (29th May 2022) - Mukherjee, Nupur; Sharma, Richa; Modi, Deepak
Abstract: A failure to achieve pregnancy after three or more embryo transfer cycles with high‐quality blastocysts is referred to as recurrent implantation failure (RIF). RIF can be due to altered uterine factors or male factors or embryo factors. Disrupted endometrial receptivity, altered expression of genes in several pathways, immunologic disturbances in the peripheral blood and/or the endometrium, and epigenetic alterations are associated with RIF. Amongst the immunologic disturbances, altered Th1/Th2 ratio, altered NK cell and macrophage numbers are observed in women with RIF. However, not all women with RIF have the same kind of immune dysfunction suggesting that RIF is a heterogeneous condition associated with varied immune responses and one size may not fit all. Thus, personalized therapies based on the immune status of the patient are being tested in women with RIF. In general, women with a high Th1/Th2 ratio are offered Tacrolimus, while intravenous IgG is recommended in women with high NK cell numbers/HLA mismatch. Women with hyperactivated immune status in the uterus are offered progesterone support, prednisolone, vitamin E, and intralipid treatment to suppress inflammation and oxidative stress, while endometrial scratching and intrauterine hCG administration are offered to women with hypo‐active immune status. There is a need for standardized tests for evaluation of immune status in patients and sufficiently powered randomized controlled trials for personalized therapies to determine which of these will be beneficial in women with RIF. Till then, the ART community should limit the use of such add‐on interventions in women with RIF.